2020
DOI: 10.1590/0102-311x00062919
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol outlets availability in school neighborhoods and alcohol use among adolescents

Abstract: This cross-sectional study investigated the association between alcohol use by adolescents and the availability of alcohol outlets in the neighborhood of public schools. We collected primary data including variables at individual and school neighborhood level. Multilevel logistic regression was used to estimate odds ratio (OR) with a 95% confidence interval (95%CI) for alcohol use with the exposure variables. A total of 18.4% (95%CI: 13.2; 24.1) of adolescents reported using alcohol, which was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In line with this, outlet density was consistently linked to higher levels of underage alcohol consumption [45, 48, 116–125]. This association was observed for both on‐ and off‐premises retailers [45, 116–118] and across multiple countries, including Australia [45, 123, 124], Brazil [119, 120, 122], New Zealand [118] and the United States [116, 117, 121, 126]. The association between outlet density and level of alcohol consumption was found to be stronger in adolescents than in the general population, suggesting adolescents may be particularly susceptible to the presence of alcohol outlets in their environments [117].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In line with this, outlet density was consistently linked to higher levels of underage alcohol consumption [45, 48, 116–125]. This association was observed for both on‐ and off‐premises retailers [45, 116–118] and across multiple countries, including Australia [45, 123, 124], Brazil [119, 120, 122], New Zealand [118] and the United States [116, 117, 121, 126]. The association between outlet density and level of alcohol consumption was found to be stronger in adolescents than in the general population, suggesting adolescents may be particularly susceptible to the presence of alcohol outlets in their environments [117].…”
Section: Resultsmentioning
confidence: 77%
“…Living near both these kinds of alcohol outlets has been associated with underage people seeing more alcohol‐related stimuli in their environments [78, 116], and as such both types were included in this review due to their potential to normalise alcohol use for minors [45, 116, 124]. In line with this, outlet density was consistently linked to higher levels of underage alcohol consumption [45, 48, 116–125]. This association was observed for both on‐ and off‐premises retailers [45, 116–118] and across multiple countries, including Australia [45, 123, 124], Brazil [119, 120, 122], New Zealand [118] and the United States [116, 117, 121, 126].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with Morrison and colleagues, Martins et al [37], in a convenience sampling method, discovered that binge drinking among students often occurs as a result of the density of alcohol outlets near the school; however, the convenience sample was not sufficient enough to be representative [75]. Correspondingly, a cross-sectional study with a randomly drawn sample from Curitiba's public schools conducted by Cardoza et al [41] showed an agreement with the mentioned association between adolescents' consumption and the alcohol outlet density, where it reported that a higher density of alcohol outlets is positively associated with more consumption, and adolescents in schools located further than 250 m away from alcohol outlets were had lower consumption of alcohol.…”
Section: Proximity To Alcohol Outletsmentioning
confidence: 77%
“…Socioeconomic exposure can be extended to the level of education, employment, type of profession, and monthly income, as all these factors may expose individuals to certain alcohol consumption patterns, including risky consumption. In terms of alcohol consumption in general, it was reported that men with a higher socioeconomic status were more likely to drink alcohol and smoke [62], professionals and mangers had more drinking occasions than semi-skilled and unskilled manual workers [29], and higher chances of alcohol consumption could be found among students who worked [41].…”
Section: Socioeconomic Exposurementioning
confidence: 99%